Invigorasi dan Pengurangan Pupuk N untuk Meningkatkan Pertumbuhan, Hasil, dan Mutu Benih Kacang Bambara - Fitriesa, Sophia; Ilyas, Satriyas; Qadir, dan Abdul (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2016)
ABSTRACTBambara groundnut can be cultivated in marginal land, however, its productivity is still low. In order to increase productivity, high quality seed must be used. The objective of the experiment was to evaluate the effects of seed invigoration using matriconditioning plus Rhizobium sp. and fungicide and reduction of N fertilizer on plant growth, yield, and quality of bambara groundnut seed. The experiment was conducted at Experimental Station in Cikarawang, green house in Cikabayan, and Seed Health Laboratory, Bogor Agricultural University from June 2013 until March 2014. This experiment was arranged in a split plot design according to completely randomized block design. The first factor was N fertilizer. Four levels of N fertilizer used were 0, 15.35, 30.7, 46.04, and 61.39 kg N ha-1. The second factor was seed invigoration. Seed invigoration consisted of without invigoration treatment (untreated), matriconditioning plus Rhizobium sp. and fungicide, matriconditioning plus Rhizobium sp., and matriconditioning plus fungicide. Result of the experiment indicated that matriconditoning plus Rhizobium sp. and fungicide improved plant growth (number of leaves, number of stem, nodule dry weight, root dry weight, and leaf dry weight), yield (weight of seed), and seed vigor (index of vigor). Matriconditioning plus Fungicide treatments significantly decreased the infection level of diseases on seed. Fertilizer application at the rate of 30.7 kg N ha-1 (half of optimum dose) was recommended because it showed the best result in pod fresh weight and dry weight, and seed weight.Keywords: benomyl, fertilization, fungicide, matriconditioning, Rhizobium sp.